2007
DOI: 10.1111/j.1369-7625.2007.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of health professionals' intention to screen for decisional conflict in clinical practice

Abstract: Objective To identify the determinants of the intention of physicians to screen for decisional conflict in clinical practice.Background Screening for decisional conflict is one of the key competencies when educating health professionals about shared decision making. Theory-based knowledge about variables predicting their intention to screen for decisional conflict in clinical practice would help design effective implementation interventions in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 52 publications
(108 reference statements)
1
18
0
1
Order By: Relevance
“…This factor is most often associated with the intention among health professionals [15]. Also, a study based on the TPB that also explored other SDM–related behaviours among healthcare professionals revealed that this factor was the most significant predictor of the intention [38]. With regard to individual control beliefs, lack of time and lack of interviewing skills were those common to both behaviours in significantly explaining intention.…”
Section: Discussionmentioning
confidence: 92%
“…This factor is most often associated with the intention among health professionals [15]. Also, a study based on the TPB that also explored other SDM–related behaviours among healthcare professionals revealed that this factor was the most significant predictor of the intention [38]. With regard to individual control beliefs, lack of time and lack of interviewing skills were those common to both behaviours in significantly explaining intention.…”
Section: Discussionmentioning
confidence: 92%
“…Accordingly, decisional conflict screening matches patients' needs to the level of decision support required. Evidence suggests that the intention of primary care practitioners ( n = 122) to involve patients in decision making is strengthened following an intervention that involved a workshop on shared decision making and the use of the decisional conflict scale as a clinical screening tool (Légaré 2007; Légaré et al 2006a). Other factors influencing practitioners' role in engaging patients to participate in decision making included their attitudes about shared decision making, perceived control over their behaviors, shared decision making practices of others within their practice environment, and involvement in continuing education.…”
mentioning
confidence: 99%
“…Designed on the basis of previous exploratory work, 29,31–33 DECISION+ is a theory‐based, continuing professional development program made up of three main components: (i) interactive workshops and related material; (ii) reminders of expected behaviours; and (iii) feedback to FPs on the agreement between their decisional conflict and that of their patients 25 …”
Section: Methodsmentioning
confidence: 99%